CLIPPERS. Three clinical cases and review - L. N. Prakhova; A. S. Parfyonova; Zh. I. Savintseva; A. G. Ilves; E. V. Bubnova; V. S. Krasnov; A. M. Tarasova; N. A. Totolyan (Бюллетень сибирской медицины)
CLIPPERS (Chronic lymphocytic inflammation with pontine perivascular enhancement responsive to steroids) is a rare inflammatory disease of the central nervous system, during which the pons of the brain is damaged. This disease was described for the first time in 2010 by S.J. Pittock et.al. At present, there have been around 50 described cases of the disease. Up to the present moment, there are difficulties diagnosing this disease. In the article, a literature review and three clinical cases are presented. Furthermore, the necessity of further research is shown for improving the accuracy and specificity of the diagnostic criteria, as well as for defining biomarkers and developing algorithms of effective therapy.